2022
DOI: 10.1186/s12913-022-07553-x
|View full text |Cite
|
Sign up to set email alerts
|

Over-the-counter sale of antibiotics during COVID-19 outbreak by community pharmacies in Saudi Arabia: a simulated client study

Abstract: Background Recent studies have reflected increased global concern regarding the possible acceleration of bacterial resistance secondary to the reported overuse and misuse of antibiotics during the COVID-19 pandemic. Therefore, this study aimed to investigate the nonprescribed sale of antibiotics by community pharmacies in Saudi Arabia during the COVID-19 outbreak and the pharmacists’ skills in triaging COVID-19 suspects. Methods Herein, 120 pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…This high rate of antibiotic use is unsurprising given the inappropriate and empiric prescribing of antibiotics without proper diagnosis or prescription, which is prevalent in both community and hospital settings in Kenya even outside of the pandemic period [ 17 , 21 ]. This finding is consistent with previous studies describing high rates of inappropriate antibiotic prescription in community pharmacies in Indonesia [ 22 ], Tanzania and Uganda [ 23 ], Saudi Arabia [ 24 ] and Russia [ 25 ], as well as among the general public to prevent or manage COVID-19 [ 14 , 26 , 27 ]. A recent metanalysis of global studies reported a pooled prevalence of 74.6% antibiotic usage amongst hospitalised COVID-19 patients [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…This high rate of antibiotic use is unsurprising given the inappropriate and empiric prescribing of antibiotics without proper diagnosis or prescription, which is prevalent in both community and hospital settings in Kenya even outside of the pandemic period [ 17 , 21 ]. This finding is consistent with previous studies describing high rates of inappropriate antibiotic prescription in community pharmacies in Indonesia [ 22 ], Tanzania and Uganda [ 23 ], Saudi Arabia [ 24 ] and Russia [ 25 ], as well as among the general public to prevent or manage COVID-19 [ 14 , 26 , 27 ]. A recent metanalysis of global studies reported a pooled prevalence of 74.6% antibiotic usage amongst hospitalised COVID-19 patients [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…We have seen in the study of Khojah that during the recent COVID-19 pandemic, 15.8% of pharmacies in Saudi Arabia dispensed an antibiotic without a prescription, higher than seen in the study of Alshreedy et al (2020) at 12.1% of patients with pharyngitis, with a similar proportion in the study of Al-Tannir et al ( 20 , 24 , 38 ). However, in the current study, the percentage was slightly higher at 18%, indicating a possible lax in the current monitoring of community pharmacies.…”
Section: Discussionmentioning
confidence: 50%
“…However, we are aware that inappropriate practices can return if over time there is less monitoring of community pharmacy activities coupled with continued pressure from patients to dispense antibiotics without a prescription ( 21 23 ). Such pressures were heightened during the recent COVID-19 pandemic in Saudi Arabia ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, all prescriptions were issued from private clinics and antibiotic combinations were given to 74% of home-isolated patients for a maximum of two weeks [ 30 ]. The second study conducted in Saudi Arabia and stated that 15.8% of pharmacists were convinced to sell non-prescribed antibiotics to the demands of the customers; however, there are restrictions on dispensing antibiotics without prescriptions that have been developed in the recent years [ 31 ]. In the third study, in Jordan, the dispensing of azithromycin without prescriptions was significantly higher during COVID-19, 127% higher than before the pandemic [ 32 ].…”
Section: Resultsmentioning
confidence: 99%